INDIAN KNOWLEDGE SYSTEM IN CORPORATE WELLNESS: ALIGNING PROFITABILITY WITH EMPLOYEE WELL BEING - Kaur, Rajeev (ShodhKosh: Journal of Visual and Performing Arts, 2024)
"The greatest weapon against stress is our ability to choose one thought over another." — William James Three principal factors continue to shape contemporary corporate work spaces: acute competition, unceasing work demands, and high-pressure environments. Not only does chronic workplace stress undermine employee well-being, it also precipitates drop in productivity, increased absenteeism, & higher attrition rates. This ensures that stress management remains critical to organizational success. In their pursuit of holistic growth, organizations today acknowledge the need for sustainable frameworks balancing productivity with employee well-being. Indian Knowledge Systems (IKS), rooted in Yoga, Ayurveda, Meditation, and Vedantic wisdom, offer time-tested ways to achieve a harmonious workplace, by cultivating physical, mental, and emotional resilience. This paper offers a qualitative analysis of how integration of Indian traditions into corporate environments may facilitate a stress-free work culture. To this end, it covers the philosophical crux of IKS, as well as its relevance in modern corporate settings: the emphasis is on the principles of balance, self-awareness, and ethical leadership. By way of practical adoption of mindfulness-based practices in global corporations, this study demonstrates how IKS can enhance emotional intelligence, resilience, and a balanced workplace. Through a structured framework, the paper illustrates how Yoga and Ayurveda-inspired health programs, meditation and mindfulness training can augment physical well-being and mental clarity. By inculcating self-regulation and work-life harmony, Vedantic principles provide emotional stability, while Dharma-driven leadership encourages corporate governance that is ethical, compassionate and sustainable. This study advocates for a paradigm shift in organizational structures. It urges businesses to adopt holistic well-being practices, in line with traditional Indian wisdom. By way of such non-intrusive yet transformative practices, companies can create a supportive, balanced, high-performance work culture. In conclusion, the convergence of IKS and corporate wellness presents a chance to positively redefine work environments; this will ensure that success is no prioritizes only productivity, but also employee fulfilment and overall sustainability.